If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = x + -3x + -2 Reorder the terms: 10 = -2 + x + -3x Combine like terms: x + -3x = -2x 10 = -2 + -2x Solving 10 = -2 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 10 + 2x = -2 + -2x + 2x Combine like terms: -2x + 2x = 0 10 + 2x = -2 + 0 10 + 2x = -2 Add '-10' to each side of the equation. 10 + -10 + 2x = -2 + -10 Combine like terms: 10 + -10 = 0 0 + 2x = -2 + -10 2x = -2 + -10 Combine like terms: -2 + -10 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| 14-2(3a+1)=6(4+a) | | 6t^2-7x-5=0 | | 0=-2x+x+7 | | -[3x-(2x+6)]=-6-[3(2x-5)-3x] | | 255=.5x+.03x | | -7y=258 | | -4-7x+5x=2 | | x2/3-6x1/3+5=0 | | x2/3-6x1/3+5 | | 9y(y+3)=9y-5 | | 4(6-z)-34=26z-5(2+6z) | | 6+4x-5x=-6 | | 6x-36=-9(x-1) | | f(x)=-5x^2+8x+5 | | -5(2r+3)=3 | | 16x^2+88x+224=0 | | f/3+8=16 | | 3n+4=n+20 | | 2x^2+11x+28=0 | | 11(t-3)+3t=7(2t+3)-9 | | (-5+7i)+(5-2i)= | | 0.40=g/22+0.146 | | x+2x+x+1=34 | | x=22.5(4)+0.1(620) | | A=U+Urt | | 25.89=3.74x+7.19 | | -2x+6y=10 | | 49-10=x | | 49-10=10 | | 49-10=10 | | -15=x-12/2 | | x+33.2+x+x+33.2+23.3=191.7 |